MUSE EXISTENCE IN MILLENNAL ERA TOURISM INDUSTRY: A POSTMODERN OVERVIEW - Diwyarthi, NDM Santi; Eddy, Wayan Tagel (International Conference on Cultural Studies, 2019)
Bali, including museums, is involved in the millennial era tourism industry. Museum management can no longer be inclusive without borderless and out of the box analysis and application. This research analysis existence of museum in industrial tourism at millennial age. The research method is quantitative and qualitative, using research instruments in the form of questionnaires, interviews, documentation studies, with a population of museum visitors in Bali.The results showed that most of the guests who visited the museum were people who had studied museum related information first, namely 52 percent, 52 percent would write the story of their trip to visit the museum, 80 percent would promote the existence of the museum through internet media, 92 percent knew the museum's history that would visited and its founder, 60 percent will promote back to others. 40 percent will return to visit the same museum